2010
DOI: 10.1182/blood-2009-09-242438
|View full text |Cite
|
Sign up to set email alerts
|

Lenalidomide treatment promotes CD154 expression on CLL cells and enhances production of antibodies by normal B cells through a PI3-kinase–dependent pathway

Abstract: Chronic lymphocytic leukemia (CLL) involves a profound humoral immune defect and tumor-specific humoral tolerance that directly contribute to disease morbidity and mortality. CD154 gene therapy can reverse this immune defect, but attempts to do this pharmacologically have been unsuccessful. The immunemodulatory agent lenalidomide shows clinical activity in CLL, but its mechanism is poorly understood. Here, we demonstrate that lenalidomide induces expression of functional CD154 antigen on CLL IntroductionChron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
71
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 109 publications
(77 citation statements)
references
References 48 publications
3
71
3
Order By: Relevance
“…76 Treatment of CLL patients with lenalidomide resulted in upregulation of cell-surface CD154 and generation of antibodies to cell-surface Ror1 protein tyrosine kinase. 77 These observations suggested that lenalidomide's mode of action may be partly dependent on reversing the immune dysfunction characteristic of CLL cells. This immunologically based mechanism is probably at least partially independent of functional p53.…”
Section: Therapeutic Strategies For Cll Patients With a Dysfunctionalmentioning
confidence: 96%
“…76 Treatment of CLL patients with lenalidomide resulted in upregulation of cell-surface CD154 and generation of antibodies to cell-surface Ror1 protein tyrosine kinase. 77 These observations suggested that lenalidomide's mode of action may be partly dependent on reversing the immune dysfunction characteristic of CLL cells. This immunologically based mechanism is probably at least partially independent of functional p53.…”
Section: Therapeutic Strategies For Cll Patients With a Dysfunctionalmentioning
confidence: 96%
“…A striking finding from this study is that CLL patients possess the ability to form anti-LCP1 immunoglobulin (IgG) despite the lack of IgG-based immunity to strong vaccine Ag (tetanus). This suggests that a strong LCP1 autoimmune response is active in spite of the profound immune dysfunction that is a hallmark of CLL (that impacts on T-cells 5 and B-cell effector functions 6 Ag-specific manner. 7 The significant accumulation of CLL cells during disease progression could cause elevated production of exosomes and increase their ability to present Ag (representing chronic "exosomeantigen presentation").…”
Section: Queen Mary University Of Londonmentioning
confidence: 99%
“…The immunomodulatory agent (iMiD) lenalidomide has shown impressive clinical trial results in CLL by enhancing both anti-tumor specific granzyme-B 1 T-cells 4 and B-cell immunity (humoral autoimmunity against CLL-membrane Ags, such as receptor tyrosine kinase-like orphan receptor, ROR1). 6 Taken together, targeted KIs that inhibit protumor TME signaling may show synergistic activity with biological therapies (future use of clinical anti-LCP1 mAb) or immunotherapy (lenalidomide or programmed-cell death-1, PD-1 immune checkpoint blocking mAbs). 3 This combinatorial approach could inhibit CLL homing to the TME (blocking BCRsignaling and LCP1 activation), while activating anti-tumor immunity against residual tumor membrane-or exosomeassociated Ags including LCP1.…”
Section: Queen Mary University Of Londonmentioning
confidence: 99%
“…Lenalidomide, an iMiD currently under investigation, was shown to bolster humoral autoimmunity against known CLL-specific membrane antigens. 4 The significance of this autoimmune signature is unknown; however, humoral immunity has previously pinpointed a number of relevant tumor targets including p53, Her2/neu, WT1, MUC1, NY-ESO-1, and, in CLL, ROR1. [5][6][7][8] In terms of CLL therapy, ROR1 is currently under development as both a monoclonal antibody target and chimeric antigen receptor epitope-based therapeutic.…”
Section: Introductionmentioning
confidence: 99%
“…9 Curiously, proteomic identification of ROR1 was serendipitous with the identification of autoantibody responses against the epitope in CLL patients. 4,8 In CLL, oncogenic signaling derived from multicellular interactions within the specialized niche environment drive the proliferation of an otherwise quiescent leukemic clone. 10 In this respect, receptors, ligands, and other membrane-associated proteins represent potential therapeutic targets, as they are the initiators of intracellular signaling, microenvironment homing, proliferation, and survival.…”
Section: Introductionmentioning
confidence: 99%